The Effect of Strategic Agility and Digital Transformation on Strategic Renewal: An Empirical Study of Private Primary Health Care Services in Indonesia - Austiko, Muhammad Umar; Anas, Eka Pria (Amkop Management Accounting Review (AMAR), 2026)
This study is motivated by intensifying competition and rising patient expectations for fast, accessible, and digitally enabled services in private health clinics, especially in urban Indonesian cities. A research gap persists because most prior work focuses on hospitals or macro-level analyses, while quantitative evidence at the main-clinic level remains limited. We conducted a cross-sectional survey of 142 respondents and estimated the structural model using PLS-SEM. The results show that digital orientation and digital intensity positively influence strategic agility and digital transformation, with digital intensity exerting the stronger effect, particularly on digital transformation. The mediating role of digital transformation is supported, whereas strategic agility's mediation is not. The study explains that the combination of a clear digital orientation, sustained digital investment intensity, and end-to-end execution of digital transformation is the most significant driver of strategic renewal. Managerial implications highlight the need to institutionalize digital orientation, allocate dedicated digital budgets, run cross-functional transformation programs, and foster a collaborative digital culture to accelerate execution amid competitive pressure and growing customer demands.